Testicular Morphological and Ultrasonographic Characterization of Male Gray Brocket Deers (Mazama gouazoubira) in Different Reproductive Status - de Souza Cunha, Duanny Murinelly; Barbosa de Souza, Mirley; Farias Brito, Bruna; Lima Torres, Vítor; Gothardo Pereira Nunes, Thales; Tavares, Samuel Salgado; Viana, Daniel de Araujo; Machado da Silva, Lúcia Daniel; Costa Pereira, Leda Maria; Alves Teixeira, Dárcio Ítalo (Acta Scientiae Veterinariae, 2019)
Background: Gray brocket deer (Mazama gouazoubira) populations have been declining due to human intervention. Yet, only a few studies have assessed ultrasonographic testicular characteristics in cervids. Considering the relevance of monitoring testicular size, blood flow, and parenchyma, the present study aims to establish baseline information on scrotal circumference, testicular volume, and spectral Doppler parameters, to describe differences among adult male gray brocket deer in different reproductive status, and to correlate ultrasound parameters with testes size measurements. Materials, Methods & Results: Six adult male gray brocket deers were used in the study. Scrotal circumference and testicular volume were measured. B mode ultrasound images of testes (longitudinal and cross-sectional views) and epididymes were subjected to computer-assisted analysis, obtaining the numerical pixel values (NPV) and pixel standard deviation (PSD). Using spectral Doppler, supratesticular artery blood flow velocities (peak systolic velocity - PSV, end diastolic velocity - EDV, time-average maximum velocity - TAMAX, resistivity - RI and pulsatility indices - PI) were obtained. Semen was analyzed through total motility, vigor, and concentration tests. Three animals were normospermic (F+ group) and three were oligo/azoospermic (F- group). Groups were compared using were compared using a one-way ANOVA or Kruskal-Wallis followed by Student-Newman-Keuls (SNK) test. Ultrasound parameters were correlated to testes size parameters using Pearson’s correlation for parametric variables and Spearman’s correlation for non-parametric variables. F+ group presented significantly higher scrotal circumference (14.57 ± 1.19 cm), testicular volume (26.18 ± 4.94 cm3), and testes cross-sectional NPV (69.88 ± 24.00) and PSD (10.78 ± 3.42) than group F- (NPV: 28.26 ± 13.75, PSD: 6.70 ± 1.84). No significant differences were observed between the groups regarding the spectral Doppler ultrasound parameters. Significant correlations were observed between scrotal circumference and longitudinal (r = 0.76) and cross-sectional testes NPV (r = 0.89), and testicular volume was correlated with longitudinal (r = 0.78) and cross-sectional testes NPV (r = 0.91) and with cross-sectional testes PSD (ρ = 0.82). Discussion: Increased testicular echogenicity (higher NPV) has been positively associated with improved testicular growth, cell population expansion, inner and outer seminiferous tubules diameter, spermatids percentages and testis weight. In addition, more heterogenous testes (higher PSD) were associated with higher sperm output. It was suggested that the animals in group F- had compromised testicular development and spermatogenesis. The correlation observed between testes NPV and scrotal circumference was proposed to be associated with seminiferous tubules impairment. The F- group showed lower testicular volume, NPVs and PSDs in cross-sectional testicular images, suggesting higher protein levels and lower lipid contents were present in their parenchyma, influencing in testicular echogenicity and echotexture. No differences in spectral Doppler parameters were observed between the two groups. Also observed in stallions. However, PSV, EDV, TAMAX could be potential infertility indicators in other mammalians. These different results may be due to different locations of the evaluated vessel, species and techniques, age, ambient temperature, pathological conditions, and anaesthesia. Thus, it is suggested that scrotal circumference, testicular volume, and testes NPV are good indicators of male reproductive health in gray brocket deer and may help with better male selection in the species.